PLANNING FOR THE DEVELOPMENT OF A DRINKING WATER DISTRIBUTION SYSTEM NETWORK IN SUNGAI PINYUH - Muhammad, Vira Fadila; Kadaria, Ulli; Purnaini, Rizki (Jurnal Teknik Sipil, 2024)
The increasing water demand due to population growth and territorial expansion has significantly outpaced the natural water supply in Sungai Pinyuh, Kalimantan Barat. This sub-district, part of the Mempawah Regency, faces challenges such as insufficient access to clean water, deteriorating pipe infrastructure, and environmental pollution affecting water quality. To address these issues, a study has been undertaken to plan a comprehensive development of the drinking water distribution system in Sungai Pinyuh, guided by the Regional Regulation of Mempawah Regency No. 3 of 2014. The planning utilizes EPANET software, a tool developed by the U.S. Environmental Protection Agency (EPA), which allows for the simulation of dynamic conditions in the water distribution system. EPANET helps create detailed maps of the pipe network, determine pump and reservoir locations, and specify pipe characteristics. The software"™s ability to simulate various scenarios, such as changes in demand or disruptions, is crucial for ensuring a reliable water supply. The analysis incorporates primary data from field observations and secondary data from population statistics and existing water supply documents. The proposed distribution system will employ HDPE pipes of various diameters and a pump with a capacity of 200 L/s and a head of 5 meters. Simulation results indicate that the system's velocity, ranging from 0.3 to 0.72 m/s, and other parameters, such as head loss and pressure, are within acceptable limits. Additionally, reservoir capacity planning is based on the maximum daily water demand, with a calculated capacity of approximately 3,347.839 m ³ to ensure adequate supply. This study provides a strategic framework for improving the drinking water distribution system, addressing current deficiencies, and preparing for future needs.